Towards Agentic Personal Health and Organizational Domain Coordination in Occupational Nutrition - Röhl, Kevin Nils; Alt, Rainer; Wirsam, Jan (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Workplace meal choices shape dietary behavior and health outcomes, while individuals increasingly generate health-related data through wearables. Although both domains relate to the same meal event, they remain digitally separate because they operate under different governance conditions and data sensitivities. This creates a coordination problem: individuals lack structured access to organizational meal information, while meal-service providers should not access raw personal health data. This paper develops a coordination model for cross-domain interaction between the personal and organizational domains. Drawing on coordination theory, the model specifies how locally computed personal indicators and organizational meal-related information can interact within a governing coordination infrastructure centered on the meal event as the unit of coordination. A prototype instantiation illustrates the design through bounded coordination artifacts and tool-mediated interaction. An initial controlled benchmark indicates the technical feasibility of the approach, while questions of real-world adoption and organizational impact remain for future research.